Pembelajaran Ilmu Gizi Olahraga Berbasis Blended Learning pada Mahasiswa Pendidikan Jasmani, Kesehatan, dan Rekreasi - Indra Duwi Kristiono; Wasis Djoko Dwiyogo; Imam Hariadi (Graduate School of Universitas Negeri Malang, 2019)
Abstract: The purpose of this research and development is to produce a learning product based on blended learning (face-to-face, offline, and online) in sports nutrition science courses. The development of blended learning-based sports nutrition science learning is used by researchers using blended learning-based research models for learning outcomes in problem solving. The results of the research on effectiveness tests were obtained by researchers from 3 meetings that had been carried out by researchers. Effectiveness test data: at the first meeting: the average value of the student class obtained the value of letter B (74.85%). Second meeting: the average value of the student class is obtained by the letter A (84%). At the third meeting: the average value of the student class was obtained